2021
DOI: 10.3389/fgene.2021.654869
|View full text |Cite
|
Sign up to set email alerts
|

Association of Extracellular Signal-Regulated Kinase Genes With Myopia: A Longitudinal Study of Chinese Children

Abstract: Graphical AbstractThe genes in the miRNA-target gene network represent the intersection of the target genes and the genes from String that had direct or indirect interaction relationships with significant genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…In this study, the genotype frequency and allele frequency of SNP rs939658 and rs4778879 of the RASGRF1 gene between the myopia group and the control group were not significantly different, but the genotype frequencies and allele frequencies of the rs8033417 locus of the RASGRF1 gene were significantly different between the two groups, in which the risk of high myopia was significantly higher in C allele carriers than in T allele carriers, indicating that the C allele of the rs8033417 locus was associated with myopia. The RASGRF1 gene, a protein-coding gene localized at 15q25.1, is highly expressed in neurons and the retina, and its expression is regulated by retinol and muscarinic receptors and plays an important role in retinal function and enhanced visual process [ 14 , 15 ]. Defects in the RASGRF1 gene cause impaired regulation of retinol and muscarinic receptors, resulting in impaired visual development and increased risk of high myopia [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the genotype frequency and allele frequency of SNP rs939658 and rs4778879 of the RASGRF1 gene between the myopia group and the control group were not significantly different, but the genotype frequencies and allele frequencies of the rs8033417 locus of the RASGRF1 gene were significantly different between the two groups, in which the risk of high myopia was significantly higher in C allele carriers than in T allele carriers, indicating that the C allele of the rs8033417 locus was associated with myopia. The RASGRF1 gene, a protein-coding gene localized at 15q25.1, is highly expressed in neurons and the retina, and its expression is regulated by retinol and muscarinic receptors and plays an important role in retinal function and enhanced visual process [ 14 , 15 ]. Defects in the RASGRF1 gene cause impaired regulation of retinol and muscarinic receptors, resulting in impaired visual development and increased risk of high myopia [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In retinal ganglia and photoreceptors, the ERK signaling pathway is one of the downstream cascades of DA receptors that control myopia progression [20, 21]. pERK levels can be used to assess D2R-mediated signal transduction [22].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Genetic studies on high-grade myopia indeed pointed to a strong association with a missense mutation (rs3803036) in PTPRR (Hawthorne et al, 2013) and meta-analyses of PTPRR variant rs11178469 also revealed a relationship with visual refractive errors (Tedja et al, 2018). However, these associations of myopia or ocular parameters with PTPRR were not supported by studies involving Japanese (Yoshikawa et al, 2014) and Chinese (Xiao et al, 2021) cohorts. Expansion of data and inclusion of additional ethnic groups may clarify this putative contribution of PTPRR to myopia risk factors.…”
Section: Ptpn5 Ptpn7 and Ptprrmentioning
confidence: 98%